The potential benefits of rainwater harvesting for households in the Jaffna peninsula [Abstract only] - Rink, Paul; Manthrithilake, Herath (2015)
Recent development activities in the Jaffna Peninsula are threatening the viability of the region's natural groundwater supply. Rainwater Harvesting (RWH) represents one important approach to remedying this situation. By accumulating freshwater during Jaffna's wet season, household RWH systems can supply drinking and cooking water for use during the water-limited dry season. Additionally, a RWH calculator created by the International Water Management Institute (IWMI) can be used to customize a RWH system for each family given particular household parameters such as rooftop size and daily extraction rate. When paired with cost estimates for tank construction, a RWH installation cost-benefit analysis can be determined for either a specific household or for a collection of households within the Jaffna region.